Selective Complex Precipitation for Ferro-Chrome Separation From Electroplating Sludge Leaching Solution - Jinhui, Li; Ying, Wang; Yudong, Wang; Yang, Gao; Yang, Yang; Ruixiang, Wang (Frontiers in Chemistry, 2021)
In this paper, aiming at the problem of chrome-iron separation in electroplating sludge, the separation of ferrochrome by complexation and precipitation with benzoic acid as complexing agent is proposed. The optimal conditions consisted of a 1: 3 molar ratio of Fe3+: C6H5COOH, a reaction temperature of 30 ℃, a final pH of 2.5 and a reaction time of 2 min. The separation rate of the iron was 97.38% and the rate of loss of chromium was only 3.59%. The ferrochromium separation products were analyzed by XRD, fluorescence spectroscopy, infrared spectroscopy and H NMR Spectroscopy in order to study the mechanism of precipitation. The results showed that benzoic acid preferentially forms a complex with iron and iron benzoate precipitates with an increase pH. The iron benzoate crystals have a fine particle size, settle rapidly and are easy to filter. The separation of Cr 3 + / Fe3 + was successful using our methodology.